Survei Tingkat Pengetahuan Program Merdeka Belajar Kampus Merdeka Pada Populasi Mahasiswa Program Studi Bahasa Dan Kebudayaan Inggris Universitas Al Azhar Indonesia - Thafhan Muwaffaq; Era Bawarti (Universitas Al Azhar Indonesia, 2022)
This study measures the level of acquired information about MBKM Programs from the Ministry of Education, Culture, Research, and Technology among the students of the English Language and Culture Study Program at the University of Al-Azhar Indonesia. It employed a quantitative method in which data was drawn from a population survey. The population survey was conducted using the Spadadikti questionnaire for data collection. This study looks into particular data in response to question 1, that is to what extent students are aware of Merdeka Belajar Kampus Merdeka (MBKM) policy. The response data were attained on the Likert Scale. The population consisted of students who were registered as active students for the academic year 2015-2021 (first semester, third semester, fifth semester, and seventh semester). The first two semesters were classified as “MBKM non-targeted students” whereas the later semesters were “MBKM-targeted students”. This study hypothesized that MBKM-targeted students would likely be more knowledgeable about MBKM Programs, while it would vice versa for MBKM non-targeted students. The result suggests the level of acquired information about MBKM programs is equally low. In other words, students of English Language and Culture at the University of Al-Azhar Indonesia are not necessarily aware of the programs, regardless of whether they are intended to join them. This implies the study program has yet to find a means to socialize the information about MBKM optimally.Keywords - Culture Study Program, English Language, Information, Implementation, Likert Scale, MBKM, Non-Targeted, Survey Spadadikti, Targeted Students